Computational fluid dynamic analysis of heat transfer in oscillating flow through a heat exchanger with metal foam in a stirling engine - Muhammad Ikhwan Wahid (2017)
A computational fluid dynamic analysis of heat transfer in an oscillatory flow through a heat exchanger, subjected to a constant heat source was conducted using the local thermal equilibrium and non-local thermal equilibrium model A comparison of local surface temperature and local Nusselt number with experimental data was first done to validate the simulation model. A metal foam was introduced into the heat exchanger and the local wall surface temperature and Nusselt number were calculated. The results showed that with an introduction of metal foam causes a drop in wall surface temperature along the heat exchanger. Local Nusselt number also increased, showing that having a porous medium in a heat exchanger improves heat transfer properties.A study of heat transfer properties at different levels of foam porosity was conducted. Results showed that at low porosity percentages, the surface area to volume ratio of air in contact with the foam is the largest. This accounted for the lower surface wall temperature at lower porosity levels, and subsequently a much efficient heat transfer at lower porosity level. The effects of oscillatory amplitude and oscillatory frequency on heat transfer efficiency in the heat exchanger were also studied. Results showed that for both oscillatory amplitude and oscillatory frequency, an increase in both components resulted in an overall decrease in local surface temperature along the porous wall. This in turn resulted in an improvement in heat transfer properties as local Nusselt number along the wall is increased when a higher oscillatory frequency or a higher velocity amplitude was used. A study of effects of the effective thermal conductivity of porous foam on heat transfer properties was done. An increase in thermal conductivity from 59 (W/m.K) through 280 (W/m.K) showed an increase in wall Nusselt number along the porous wall.